(untitled) (Third Sector Social Economic Review, 2019)
This study aims to give a general account of the ethics, values, principles and practice standards developed in Australia for the social work profession. To this end, a summary of the standards developed and matured by Australian Association of Social Workers (AASW) through workshops between 2000-2018. In addition, AASW has developed principles and standards for practice, supervision, school social work and mental health professionals. To depict an overall picture, this study presents briefly AASW’s Ethics Code, Practice Standards, Practice Standards for School Social Work, Practice Standards for Mental Health Social Workers, and Supervision Standards. As a consequence, the study is thought to contribute significantly to the social work literature in that it presents the country profile in terms of social work professional standards.